STATUS OF PLANT DIVERSITY IN INDIA: CHALLENGES AND CONSERVATION EFFORTS - Hemant Sharma and Mohal Lal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
India is well known for its abundant biodiversity, of which a substantial percentage is made up of plant species. A wide variety of plant species is found in the country’s diverse ecosystems, which contribute significantly to the world's biodiversity. Plant diversity or the variety of plant species and ecosystems is vital to the health and sustainability of our planet and offers a multitude of ecological, economic and cultural benefits. Plants are essential to human well-being and the functioning of ecosystems, regulating climate, supporting agriculture and providing medicinal resources. As such, protecting plant diversity is essential for sustainable development and the survival of future generations. However, because of a variety of human activities and environmental variables, this biodiversity faces several problems. The aim of this paper is to examine the current status of plant diversity in India, the challenges it faces and the conservation initiatives being made to lessen these obstacles. This study offers insights into the significance of protecting plant diversity and describes practical conservation solutions by examining current research, efforts and policies.